ANALISIS PEMILIHAN LOKASI PENGEMBANGAN KAWASAN MINABISNIS DI KABUPATEN MUSI RAWAS - Saputra, Endra; Fitriani, Heni; Juliantina, Ika (CANTILEVER, 2016)
Musi Rawas Regency is the best fish producing district in South Sumatera. This area needs a place for fish trade and processing. This study aims to determine the location of development of minapolitan areas, as a center of sales and fish processing. There are 3 districts that can be used as an alternative location of minabisnis area development in Musi Rawas Regency , namely Tugumulyo, Purwodadi, and Muara Beliti Subdistricts. The AHP method is used to determine which location is best as minapolitan. The result of survey shows that the choice of minabisnis development area in Tugumulyo sub district has a value of 125.37, the location in Muara Beliti sub-district has a value of 44,36, and location in Purwodadi has a value of 31,30. The mapping survey in Tugumulyo sub-district also shows that this area is appropriate to de developed as a minapolitan location.